2009
DOI: 10.1159/000209866
|View full text |Cite
|
Sign up to set email alerts
|

Superior Mesenteric Artery Syndrome

Abstract: A 63-year-old female presented to our department complaining of epigastric pain, nausea and vomiting. Symptoms started after a significant loss of weight and persisted despite treatment, leading to hospitalization for dehydration and renal failure due to protracted vomiting. During hospitalization, no pathology could be identified and the patient was discharged. Symptoms persisted and she was eventually readmitted. Superior mesenteric artery syndrome was diagnosed based upon clinical suspicion and barium studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Chief complaints of the patients with SMA syndrome are epigastric pain, nausea, eructation, voluminous vomiting, and postprandial discomfort. Imaging findings in the form of barium findings are dilation of the first and second part of the duodenum with an abrupt narrowing at the third portion, delayed gastroduodenal emptying and ant peristaltic waves proximal to the obstruction which may be relieved by a change in position, especially left lateral decubitus position [12]. USG of the abdomen may be helpful in measuring the angle of the superior mesenteric artery and the aortomesenteric distance but is difficult in obese patients and those with gaseous abdomen [13].…”
Section: Discussionmentioning
confidence: 99%
“…Chief complaints of the patients with SMA syndrome are epigastric pain, nausea, eructation, voluminous vomiting, and postprandial discomfort. Imaging findings in the form of barium findings are dilation of the first and second part of the duodenum with an abrupt narrowing at the third portion, delayed gastroduodenal emptying and ant peristaltic waves proximal to the obstruction which may be relieved by a change in position, especially left lateral decubitus position [12]. USG of the abdomen may be helpful in measuring the angle of the superior mesenteric artery and the aortomesenteric distance but is difficult in obese patients and those with gaseous abdomen [13].…”
Section: Discussionmentioning
confidence: 99%
“…SMA syndrome (Wilkie's syndrome) is an uncommon and often unrecognized complication of severe weight loss (1).We report an unusual surgical presentation of a rare endocrine disorder (hypothalamic lesion) presenting with emaciation and upper intestinal obstruction. Our patient was diagnosed with SMA syndrome based on CT confirmation of a narrowed aortomesenteric angle (16°) and evidence of proximal duodenal dilatation and extrinsic compression of D3 based on an esophagogastroduodenoscopy.…”
Section: Discussionmentioning
confidence: 98%
“…Superior mesenteric artery (SMA) syndrome is a rare cause of upper gastrointestinal obstruction with prevalence in the general population of 0.03 to 0.3% (1). As a result of man's upright posture, the SMA, instead of branching off perpendicular to the abdominal aorta, forms an acute downward angle of 25 to 60° (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this type of procedure has some disadvantages. In this case, we selected Roux‐en‐Y duodenojejunostomy to avoid reverse peristalsis; it was recently reported that duodenojejunostomy with side‐to‐side anastomosis does not alleviate vomiting, possibly due to reverse peristalsis being greater than direct peristalsis in some cases . Even though creating an additional Roux‐en‐Y anastomosis might be time‐consuming, it is a more physiological reconstruction that avoids blind loop syndrome and jejunal loop twisting .…”
Section: Discussionmentioning
confidence: 99%